2011
DOI: 10.1369/0022155411398488
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Degradation of Archival Formalin-Fixed Paraffin-Embedded Tissue Sections

Abstract: The loss of antigenicity in archival formalin-fixed paraffin-embedded (FFPE) tissue sections negatively affects both diagnostic histopathology and advanced molecular studies. The mechanisms underlying antigenicity loss in FFPE tissues remain unclear. The authors hypothesize that water is a crucial contributor to protein degradation and decrement of immunoreactivity in FFPE tissues. To test their hypothesis, they examined fixation time, processing time, and humidity of storage environment on protein integrity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 28 publications
5
144
0
4
Order By: Relevance
“…Grillo F et al demonstrated that antigen loss or decay was seen in IHC of CD3, CD 31, CD117, estrogen and progesterone receptors, Ki67, p53, TTF-1, vimentin, but not in IHC of smooth muscle actin, keratins 7, 20, AE1/AE3, 34βE12, and they also showed cold storage is suitable methods for long term storage of tissue sections. 19 The importance of cold storage (at minus degrees rather than at 4 o C) was reported by other researchers, 20 and these observations were consistent with our observation of figure 3.…”
Section: Discussionsupporting
confidence: 93%
“…Grillo F et al demonstrated that antigen loss or decay was seen in IHC of CD3, CD 31, CD117, estrogen and progesterone receptors, Ki67, p53, TTF-1, vimentin, but not in IHC of smooth muscle actin, keratins 7, 20, AE1/AE3, 34βE12, and they also showed cold storage is suitable methods for long term storage of tissue sections. 19 The importance of cold storage (at minus degrees rather than at 4 o C) was reported by other researchers, 20 and these observations were consistent with our observation of figure 3.…”
Section: Discussionsupporting
confidence: 93%
“…We also previously demonstrated that the possible oxidation of endogenous and exogenous water is a key factor in the loss of antigenicity during storage of FFPE tissue. 28 On the basis of our histomorphological observations of overbleached FFPE tissue sections (data not shown), the H 2 O 2 -based bleaching method may be linked with tissue oxidation. Clearly, the exact mechanism of the H 2 O 2 -based bleaching procedure is an area for further study.…”
Section: The Melanin Bleaching Methods Enabled Dna Analysis In Archivamentioning
confidence: 80%
“…In addition to Decipher scores, we evaluated the expression levels of genes used in other published molecular signatures used for prostate cancer risk stratification, including expression signatures from Cuzick et al, 19 Klein et al, 18 and Penney et al, 20 as previously described. 5 For comparison, the RNA expression of the individual genes comprising these signatures was evaluated in both biopsy and RP samples. More than 94% of the features were higher than the LOD in all biopsy and RP samples, providing evidence of the ability of the assay to capture the biological signal of multiple prognostic signatures.…”
Section: Prostate Cancer Prognostic Signatures (Cuzick Klein Penneymentioning
confidence: 99%
“…When using formalin-fixed, paraffin-embedded (FFPE) tissue specimens as starting material, the FFPE processing causes degradation of RNA that generates challenges in using expression patterns as a clinical biomarker; the oxygen and hydroxyl radicals in formalin crosslink RNA, and the high temperatures of the wax involved in embedding the sample cause irreversible damage to RNA, with fragmentation into 150 to 200 bases long oligonucleotides. 5 Run-to-run variations in processing parameters, as well as processing and storage variations from one institution to the next, can also affect RNA levels and degradation rates in FFPE tissue specimens. Tumor heterogeneity and the limited amount of tumor in biopsy material further affect expression analyses, introducing multiple, sometimes discordant, expression signatures.…”
mentioning
confidence: 99%